Analisis Link Aggregated Group Interface Pada Switch Untuk Sistem Link Redudancy Di Universitas Widyatama - Rahman, Atep Aulia; Fauzi, Esa; Prasetyo, Bagus Alit; Utomo, Bimo Cokro (Jurnal Ilmiah Informatika Global, 2023)
Widyatama University is a Legal Entity Private Higher Education Institution under the main institution of the Ministry of Education, Culture, Research and Technology (Kemendikbudristek). Providing superior private universities is one of the results of performance, management and maintaining service quality. Link Redundancy is one of the technologies in the network that is used to maintain the stability of a network connection by using several physical network paths simultaneously. Link Redundancy is needed for performance and services to run well. Link Aggregation Group (LAG) is one of the link redundancy models whose way of working is to combine several physical interfaces into a single interface at the Layer 2 network layer (Data Link Layer). Implementation of Link Aggregation Group (LAG) makes network connections more secure by increasing bandwidth, dividing bandwidth loads, increasing network path availability, and having a minimal risk of data duplication of data errors.